THE PATIENT AND HIS OR HER DIGITAL DATA IN A “DIGITIZED” HEALTHCARE ENVIRONMENT - FLORA, Luigi (MEDECINE LEGALE DROIT MEDICAL, 2025)
While more and more citizens are using digital technology, the state is struggling to get citizens to adopt the various personal digital records that have been proposed for years, the latest of which, “my health space”, has been created by default since early 2022. This article proposes to shed light on this paradox.